2023
DOI: 10.1126/science.ade5801
|View full text |Cite
|
Sign up to set email alerts
|

Picoflare jets power the solar wind emerging from a coronal hole on the Sun

L. P. Chitta,
A. N. Zhukov,
D. Berghmans
et al.

Abstract: Coronal holes are areas on the Sun with open magnetic field lines. They are a source region of the solar wind, but how the wind emerges from coronal holes is not known. We observed a coronal hole using the Extreme Ultraviolet Imager on the Solar Orbiter spacecraft. We identified jets on scales of a few hundred kilometers, which last 20 to 100 seconds and reach speeds of ~100 kilometers per second. The jets are powered by magnetic reconnection and have kinetic energy in the picoflare range. They are intermitten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Wang et al (2022) identified 88 flux cancellation events associated with Hα spicules, out of which seven events are associated with EUV jets/spicules. Based on the statistics of the observed jets (that are on scales of a few hundred kilometers), Raouafi et al (2023) argued that they can provide sufficient mass and energy flux into the corona to explain the solar wind (see also Chitta et al 2023b). We therefore propose that such jets are due to small-scale flux cancellation reconnection driven by photospheric flux cancellation on granular scales.…”
Section: Introductionmentioning
confidence: 86%
“…Wang et al (2022) identified 88 flux cancellation events associated with Hα spicules, out of which seven events are associated with EUV jets/spicules. Based on the statistics of the observed jets (that are on scales of a few hundred kilometers), Raouafi et al (2023) argued that they can provide sufficient mass and energy flux into the corona to explain the solar wind (see also Chitta et al 2023b). We therefore propose that such jets are due to small-scale flux cancellation reconnection driven by photospheric flux cancellation on granular scales.…”
Section: Introductionmentioning
confidence: 86%
“…The Solar Orbiter-observed picoflare jets of Chitta et al (2023) are much smaller still, with spatial scales of ∼few × 100 km, which is comparable to the widths of spicules. They estimate a lower limit of the kinetic energy to be ∼10 21 erg for the picoflare jets.…”
Section: Smaller Jetlike Featuresmentioning
confidence: 94%
“…Furthermore, they argue that the magnetic switchbacks, which are localized rotations in the solar wind magnetic field that are ubiquitously detected in near-Sun Parker Solar Probe (PSP) data, could also be a consequence of the magnetic reconnection events that produce the jetlets and solar wind and are built up and triggered by fine-scale flux cancelation. Chitta et al (2023), on the other hand, use Solar Orbiter data to conclude that there are even smaller-scale features, which they call "picoflare jets," with widths ∼100 km. These observations are of a coronal hole using Solar Orbiter's EUV High Resolution Imager (HRI EUV ) at 174 Å and were taken during a close approach of 0.332 au, where the images had a spatial resolution of about 237 km.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this work is to establish a theoretical scaling law for  M w (Schröder & Cuntz 2005;Cranmer & Saar 2011;Suzuki et al 2013;Suzuki 2018;Chebly et al 2023) that aligns with both solar and stellar observations. Solar wind models generally rely on either Alfvén-wave acceleration (Ofman & Davila 1995, 1998Matthaeus et al 1999;Dmitruk et al 2002;Ofman 2004;Suzuki & Inutsuka 2005;Verdini & Velli 2007;Verdini et al 2010;Perez & Chandran 2013;van der Holst et al 2014;van Ballegooijen & Asgari-Targhi 2016;Usmanov et al 2018;Shoda et al 2019;Réville et al 2020;Matsumoto 2021;Schleich et al 2023) or loop-opening acceleration (Fisk et al 1999;Fisk 2003;Rappazzo et al 2012;Lionello et al 2016;Chitta et al 2023aChitta et al , 2023bBale et al 2023;Drake et al 2023;Kumar et al 2023;Raouafi et al 2023). Recent observations of magnetic switchbacks (Bale et al 2019;Kasper et al 2019;Bale et al 2021;Telloni et al 2022) appear to support the loop-opening scenario (Fisk & Kasper 2020;Tenerani et al 2020;Zank et al 2020;D...…”
Section: Introductionmentioning
confidence: 99%